2021
DOI: 10.3390/molecules26092433
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimicrobial, Antioxidant and Anticancer Activities of Egyptian Citrus Beebread

Abstract: In this study, Egyptian beebread (EBB) was investigated for its nutritive value, chemical composition, antioxidant properties, antimicrobial and antitumor activities. Results indicated that EBB was a good source of protein (23.58 ± 0.183 g/100 g BB), total free sugar (20.266 ± 0.930) and potassium (290.202 ± 2.645 mg/100 g). Additionally, 14 fatty acids were identified in EBB, wherein polyunsaturated and monounsaturated fatty acids represented 51.06% ± 0.09% and 9.86% ± 0.01%, respectively. The EBB extract exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 49 publications
(59 reference statements)
0
22
0
Order By: Relevance
“…Flavonoids, phenolic acids, and other antioxidant components are recognized as effective functional molecules, displaying numerous bio-pharmacological potentialities. In fact, several researchers suggest the use of bee bread as a common food preservative and bio-functional dietary supplement, or as a therapeutic strategy in the prevention of oxidative stress and associated ailments, such as cardio-metabolic, neurodegenerative, and cancerous diseases [ 46 , 51 , 52 ].…”
Section: Bee Bread Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids, phenolic acids, and other antioxidant components are recognized as effective functional molecules, displaying numerous bio-pharmacological potentialities. In fact, several researchers suggest the use of bee bread as a common food preservative and bio-functional dietary supplement, or as a therapeutic strategy in the prevention of oxidative stress and associated ailments, such as cardio-metabolic, neurodegenerative, and cancerous diseases [ 46 , 51 , 52 ].…”
Section: Bee Bread Compositionmentioning
confidence: 99%
“…In a study conducted by Didaras et al [ 84 ], it was reported that the aqueous extract of Greek bee bread was effective against Gram-positive bacteria (MIC values ranging between 3.9 mg/mL and 48 mg/mL) and against Gram-negative bacteria (MIC values ranging between 7.8 mg/mL and 90.4 mg/mL). It has also been shown that bee bread ethanolic extracts (70%, 95%, 80%, and 50%) have strong antibiotic activity against Gram-positive bacteria ( Bacillus cereus , Clostridium perfringens, Staphylococcus aureus, Bacillus Subtilis, methicillin-susceptible Staphylococcus aureus, Staphylococcus epidermidis, and Listeria monocytogene ), Gram-negative bacteria ( Haemophilus influenza, Klebsiella pneumonia, Salmonella enteric, Escherichia coli, Shigella, Salmonella typhi , and Pseudomonas aeruginosa )and fungi ( Candida albicans, Aspergillus niger , Candida glabrata, Candida tropicalis , Aspergillus clavatus, Aspergillus flavus, Aspergillus versicolor, Penicillium expansum, Penicillium chrysogenum, and Penicillium griseofulvum ) [ 52 , 85 , 86 , 87 , 88 ].…”
Section: The Bioactive Effect Of Bee Bread: In Vitro Investigationsmentioning
confidence: 99%
“…Apart from that, the investigation on the mechanisms in the activity of royal jelly as anticancer revealed that it may enhance production of cytokine from mononuclear cells to suppress the growth of U937, a leukemia cell model [138]. Meanwhile, bee bread, a bee product that is closely related to royal jelly, was also shown to have antiproliferative activities against Caco-2 and PC-3 cell lines [139]. Bee bread has also been tested against MCF-7, HeLa, HepG-2 and non-small cell lung cancer (NCI-H460), although the potency was relatively low to moderate (GI 25 > 400 to 68 µg/mL) [89].…”
Section: Anticancer Properties Of Bee Productsmentioning
confidence: 99%
“…Bee bread has also been tested against MCF-7, HeLa, HepG-2 and non-small cell lung cancer (NCI-H460), although the potency was relatively low to moderate (GI 25 > 400 to 68 µg/mL) [89]. It consists mainly of polyunsaturated and monounsaturated fatty acids [139], but the substances that are thought to be responsible for the anticancer potency are its flavonoids and polyphenolic constituents including isorhamnetin-O-glycoside, quercetin-O-glycoside, herbacetin glycosides, kaempferol, and myricetin [89].…”
Section: Anticancer Properties Of Bee Productsmentioning
confidence: 99%
“…Protein samples were acid hydrolyzed using 6 N HCl according to Peksa et al [49]. An automated amino acid analyzer (AAA 400, INGOS Ltd.) was used for determining amino acids.…”
Section: Amino Acids Profile Of Mp and Mpmcmentioning
confidence: 99%